Da Lotta continua alla religione civile. La memoria di Peppino Impastato nelle storie di quattro militanti - Matteo Di Figlia (Laboratoire Italien)
The essay studies how public memory of Peppino Impastato, killed by the mafia in 1978 in Cinisi, near Palermo, has changed in the decades up to the present day. To do so, we will follow the biographical paths of four militants of Lotta continua, the political group in which Impastato was active until 1976, which was part of the vast and complex world of the Italian left outside the Communist Party. In particular, the focus will be on the way in which the public mourning for Impastato has been interlinked with the stratification of public discourse on the mafia and with the public rites linked to other victims of Sicilian organized crime.